Biomaker evaluation for major adverse cardiovascular event development in patients undergoing cardiac Surgery - Imperiali Claudia E. (De Gruyter, 2020)
The postoperative period of cardiac surgery (CS) is associated with the development of major adverse cardiovascular events (MACEs). However, the evaluation of MACE after CS by means of biomarkers is poorly developed. We aimed to evaluate postoperative biomarkers that could be associated with MACE.